Assembly of metal-organic polyhedra into highly porous frameworks for ethene delivery - Stoeck, Ulrich; Senkovska, Irena; Bon, Volodymyr; Krause, Simon; Kaskel, Stefan (Chemical Communications, 2015)
Two new mesoporous metal-organic frameworks (DUT-75 and DUT-76) with exceptional ethene uptake were obtained using carbazole dicarboxylate based metal-organic polyhedra as supermolecular building blocks. The compounds have a total pore volume of 1.84 and 3.25 cm3 g-1 and a specific BET surface area of 4081 and 6344 m2 g-1, respectively, and high gas uptake at room temperature and high pressure.
CRIS-Team Scopus Importer:2023-03-20